Preanalytical Stability of 13 Antibiotics in Biological Samples: A Crucial Factor for Therapeutic Drug Monitoring - Paolo Dalla Zuanna; Debora Curci; Marianna Lucafò; Riccardo Addobbati; Antonella Fabretto; Gabriele Stocco (MDPI AG, 2024)
The stability of antibiotic preanalytical samples is a critical factor in therapeutic drug monitoring (TDM), a practice of undoubted importance for the proper therapeutic use of antibiotics, especially in complex management patients, such as pediatrics. This review aims to analyze the data in the literature regarding the preanalytical stability of some of the antibiotics for which TDM is most frequently requested. The literature regarding the preanalytical stability of amikacin, ampicillin, cefepime, ceftazidime, ciprofloxacin, daptomycin, gentamicin, levofloxacin, linezolid, meropenem, piperacillin, teicoplanin, and vancomycin in plasma, serum, whole blood, and dried blood/plasma spot samples was analyzed. Various storage temperatures (room temperature, 4 °C, −20 °C, and −80 °C) and various storage times (from 1 h up to 12 months) as well as subjecting to multiple freeze-thaw cycles were considered. The collected data showed that the non-beta-lactam antibiotics analyzed were generally stable under the normal storage conditions used in analytical laboratories. Beta-lactam antibiotics have more pronounced instability, particularly meropenem, piperacillin, cefepime, and ceftazidime. For this class of antibiotics, we suggest that storage at room temperature should be limited to a maximum of 4 h, storage at 2-8 °C should be limited to a maximum of 24 h, and storage at −20 °C should be limited to a maximum of 7 days; while, for longer storage, freezing at −80 °C is suggested.